InClass – an instrument to assess classroom management in inclusive and special education with a focus on heterogeneous learning groups - Lutz, Stephanie; Frey, Anne; Rank, Astrid; Gebhardt, Markus (Frontiers in Education, 2024)
Organizing lessons for heterogeneous learning groups is a challenge for student teachers and novice teachers. To observe and improve classroom management during student teaching, we have developed an assessment tool. The aim of this study is to evaluate and improve the instrument “Scale for Classroom Management in Inclusive Schools (InClass)” with data from 480 student teachers in internships at elementary or special schools in Germany and Austria. The instrument consists of three dimensions Adaptive Teaching Scale (ATS), Relationship Scale (RS), Behavior Management Scale (BMS). Confirmatory factor analyses revealed good reliable values (CFI = .97, TLI = .96, RMSEA = .06, SRMR = .04) for the three-factor InClass model and could confirm the theoretically developed scales. The latent correlations were between r = .74 and r = .63. Teachers in elementary schools also showed latent correlations between the three dimensions and their assessment of implementation of inclusive education in the school ranging from r = .51 to r = .84. In order to meet the individual needs of all students, with and without special educational needs (SEN), novice teachers in particular should be supported in dealing with heterogeneous learning groups and in using effective classroom management. Instruments such as InClass help student teachers evaluate and reflect on instruction and therefore have an important contribution to teacher education.